PERAN PESERTA DIDIK DALAM PROMOSI SENI BUDAYA DAERAH MELALUI MEDIA SOSIAL - Papadja, Anita; Suan, Elidat Binyamin; Taneo, Dersy Rejoice; Ratu, Steffi Eka Permatasari R. A; Djuka, Angela Tabita (Jurnal Abdi Insani, 2024)
This community service activity was motivated by the low participation of high school and vocational high school students in Kupang City in promoting regional arts and culture through social media. A survey revealed that students' awareness of the importance of preserving and promoting local culture was still minimal, leading to a decline in the prominence of regional arts and culture. This situation underscores the critical role of students in safeguarding and promoting regional arts and culture in the digital age.The objective of this activity was to educate students about the significance of their role in preserving regional culture and train them to utilize social media as an effective promotional tool. The methods employed in this activity included training sessions, discussions, and hands-on practice. The materials covered the role of students in promoting arts and culture, social media trends, creative content creation techniques, and the use of Google Sites to build simple websites.The results of this activity demonstrate an increase in students' understanding of the importance of their role in promoting regional culture. Students successfully created creative content and simple websites to serve as platforms for promoting arts and culture. In conclusion, social media can be a powerful tool for disseminating regional arts and culture more widely, and students, as the next generation, bear the responsibility of preserving cultural identity in this digital era.